The influence of emotional intelligence of secondary school teachers on classroom discipline strategies - Jeloudar, Soleiman Yahyazadeh; Md. Yunus, Aida Suraya; Roslan, Samsilah; Md Nor, Sharifah (Marsland Press, 2011)
The purpose of the study is to analyze level of emotional intelligence among teachers employed in government secondary schools based on selected demographic variable. The sample of the study comprised 203 teachers. The findings of the study showed that there was a significant difference in the teachers’ races (Malay, Indian and Chinese) and their emotional intelligence. The study also revealed that there were significant differences between teachers with high and moderate level of emotional intelligence in five strategies of classroom discipline used i.e. teachers with high level of emotional intelligence scored higher in the classroom discipline strategies of discussion, recognition, involvement, and hinting, whereas teachers with moderate level of emotional intelligence scored higher in the use of aggression and no significant relationship with one strategy (punishment) of classroom discipline.